Effect of Astragalus membranaceus on left ventricular remodeling in HFrEF: a systematic review and meta-analysis - Han, Xu; Yu, Ting; Chen, Xi; Du, Zhiyan; Yu, Man; Xiong, Jiang (Frontiers in Pharmacology, 2024)
Background: Left ventricular remodeling (LVR) is a key factor leading to the onset and progression of heart failure with reduced ejection fraction (HFrEF). Improving LVR can delay the progression of HFrEF and improve quality of life.Objective: To evaluate the improvement effect of Astragalus membranaceus (A. membranaceus) on LVR in patients with HFrEF.We retrieved randomized controlled trials of A. membranaceus in treating HFrEF from eight Chinese and English databases, up until October 31, 2023. To assess the quality of the literature, we utilized the bias risk tool from the Cochrane Handbook. Totally 1565 patients were included in 19 RCTs. Compared to conventional treatment (CT), the combination therapy of A. membranaceus with CT demonstrated significant improvements in LVR, specifically increasing left ventricular ejection fraction (LVEF, MD = 5.82, 95% CI: 4.61 to 7.03, p < 0.00001), decreasing left ventricular end-diastolic diameter (LVEDD, MD = -4.05, 95% CI: -6.09 to -2.01, p = 0.0001), and left ventricular end-systolic diameter (LVESD, MD = -12.24, 95% CI: -15.24 to -9.24, p < 0.00001). The combination therapy of A. membranaceus with CT also improved clinical efficacy (RR = 4.81, 95% CI: 3.31 to 7.00, p < 0.00001), reduced brain natriuretic peptide (BNP, MD = -113.57, 95% CI: -146.91 to -81.22, p < 0.00001) level, and increased 6-minute walking distance (6-MWD, MD = 67.62, 95% CI: 41.63 to 93.60, p < 0.00001). In addition, the combination therapy of A. membranaceus with CT mitigated inflammatory responses by reducing tumor necrosis factor-alpha (TNF-α, MD = -16.83, 95% CI: -22.96 to -10.71, p < 0.00001), interleukin-6 (IL-6, MD = -29.19, 95% CI: -36.08 to -22.30, p < 0.00001), and high-sensitivity Creactive protein (hs-CRP, MD = -0.98, 95% CI: -1.43 to -0.52, p < 0.0001). Notably, the combination therapy of A. membranaceus with CT did not increase the incidence of adverse reactions (RR = 0.86, 95% CI: 0.25 to 2.96, p = 0.81). Conclusion: This systematic review and meta-analysis revealed that the combination therapy of A. membranaceus with CT has more advantages than CT alone in improving LVR and clinical efficacy in HFrEF patients, without increasing the incidence of adverse reactions.